Wireless body area network using data communicationprotocol - K, Antony Kumar; Saranya Jothi, C; Ravikumar, S; Usha, V (International Journal of Engineering and Technology, 2018)
Remote Body Area Networks are relied on to expect a basic part in the field of patient-thriving checking inside the not so distant future, which increases beast thought among specialists beginning late. One of the inconveniences is to build up a protected correspondence design among sensors and clients, while watching out for the typical security and protection concerns. In this paper, we propose a correspondence planning for BANs, and outline a course of action to secure the information exchanges between introduced/wearable sensors. Our course of action accomplishes an area based access control by utilizing an entry control tree portrayed by the attributes of the information. We likewise outline two customs to safely recover the touchy information from a BAN and instruct the sensors in a BAN.